200 anos de imprensa e muitas histórias desde 1808 a 2008 (Em Tempo de Histórias, 2011)
MARTINS, Ana Luiza, e LUCA, Tania Regina de. (orgs.). História da imprensa no Brasil. São Paulo: Contexto, 2008, 304 p.